Investigation on Low Stress Scratching Abrasion Resistance Influencing Residual Stress in Nickel Chromium Alloyed Iron - Sandeep Mashetty A.; Sampathkumaran P.; Ranjitha P.; Chithirai Pon Selvan; Shridhar Deshpande C.; Avinash Lakshmikanthan; Manjunath Patel G.C. (Archives of Foundry Engineering, 2025)
In thermal power plants, advanced wear-resistant alloyed irons have been used for over three decades to enhance the longevity of parts. Ni-hard irons, high chromium irons, and HCHC materials are commonly used in components like liners, bull rig segments, and orifices. These components are exposed to various types of failures, including abrasion, erosion, corrosion, and fatigue. Nickel-chromium irons, particularly Ni-hard 4 and high chromium irons, have proven effective in extending component life. However, the impact of scratching abrasion resistance on residual stress (RS) buildup has been less studied. This research investigates the wear behavior of nickel-chromium irons, focusing on Ni-hard and high chromium-manganese iron. Abrasion loss was measured using a rubber wheel abrader according to ASTM standards, and RS was evaluated through X-ray diffraction before and after abrasion testing. Supporting analyses, including hardness testing, phase analysis, carbide morphology, and microstructural evaluations, were performed to correlate abrasion with RS data. Scanning electron microscopy (SEM) was used to assess wear phenomena. The HiCr sample displays the highest hardness and compression strength, and lowest abrasion loss, followed by NH4, HiCr5Mn, HiCr10Mn, and HiCr15Mn samples. Higher Mn content introduces more brittle characteristics into the fracture process. Among HiCrMn samples, HiCr5Mn is preferred for abrasion resistance application; on the other hand, HiCr15Mn may be suitable in the field, possessing better resistance to impact and load bearing applications.